Design and Development of Two-level Deployed and Multi-level Applied Electric Energy Substitution Effect Improvement and Business Expansion Support Software. (June 2020) - Miao, Bo; Li, Chang; Liu, Hao; Lin, Jingyi
Abstract: With the in-depth promotion of electric energy substitution and the rapid development of grid informationization, the building of systematic and integrated electric energy substitution effect improvement and business expansion support software becomes an important means to further optimize the electric energy consumption management level and realize the overall improvement of electric energy utilization efficiency. This paper introduces the design idea of this software, shows the layer structure of the platform, describes the relationships among all layers, analyzes the key technologies of the system, and researches and designs the general architecture and function modules. This platform provides the strong technical support for the state to promote the lean management of electric energy substitution and for the State Grid to develop the building of electric energy substitution service system.